The Influence of the Self-Assessment System and MSME Income Turnover on MSME Taxpayer Compliance with Emotional Intelligence as a Moderating Variable (A Case Study at KPP Pratama Makassar Utara) - Nungki Prawita Sari; Syamsu Alam; Muhammad Syafii Basalamah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
MSMEs in Indonesia are required to pay final taxes in accordance with Government Regulation No. 23 of 2018, with a tax rate of 0.5% of gross turnover. This obligation is designed to simplify the taxation process for MSMEs. This study aims to examine the influence of the Self-Assessment System and MSME Income Turnover on MSME Taxpayer Compliance, with Emotional Intelligence as a Moderating Variable. The data for this research were obtained from MSME taxpayers registered at KPP Pratama Makassar Utara who agreed to participate as respondents. This study utilized primary data collected through field research by distributing questionnaires/statements to 92 respondents. Data analysis was performed using descriptive statistical analysis and PLS (Partial Least Square). The results of the study indicate that the Self-Assessment System and MSME Income Turnover have a positive and significant effect on MSME Taxpayer Compliance. Furthermore, the positive and significant effect of the Self-Assessment System and MSME Income Turnover on MSME Taxpayer Compliance is strengthened by Emotional Intelligence.